2017
DOI: 10.2147/ndt.s128116
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the ability of cognitive and affective Theory of Mind in adolescent onset schizophrenia

Abstract: BackgroundEvidence in the literature suggests that there is an impairment of social cognition in schizophrenia. Theory of Mind (ToM) is defined as one’s ability to understand others’ wishes, beliefs, intentions, and other psychological states and thereby to judge others’ behavior, as an essential component of social cognition. However, there have been limited studies on social cognition, especially ToM in adolescent onset schizophrenia (AOS). The current study aims to investigate ToM abilities in adolescent sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…A wide range of patient groups have already been found to report impairment on at least some aspect of the Yoni Task, suggesting that this is a versatile and sensitive measure. They include samples with Parkinson’s disease (172, 173), mild cognitive impairment (173), schizophrenia (174, 175), first-episode psychosis (176), bipolar disorder (174), depression (174), obsessive–compulsive disorder (177), epilepsy (178), Huntington’s disease (179), and Tourette syndrome (100). The task has revealed selective deficits in some patient groups on ToM trials only with performance on control trials being spared [e.g., in Parkinson’s disease: Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of patient groups have already been found to report impairment on at least some aspect of the Yoni Task, suggesting that this is a versatile and sensitive measure. They include samples with Parkinson’s disease (172, 173), mild cognitive impairment (173), schizophrenia (174, 175), first-episode psychosis (176), bipolar disorder (174), depression (174), obsessive–compulsive disorder (177), epilepsy (178), Huntington’s disease (179), and Tourette syndrome (100). The task has revealed selective deficits in some patient groups on ToM trials only with performance on control trials being spared [e.g., in Parkinson’s disease: Ref.…”
Section: Resultsmentioning
confidence: 99%
“…(197, 368)] and neurophysiological studies (369), and has been presented with illustrations to help control for working memory demand (370). Deficits in understanding faux pas can be found in epilepsy (especially temporal lobe epilepsy) (157, 159, 338, 371376), substance misuse (377), Parkinson’s disease (378, 379), multiple sclerosis (380, 381), schizophrenia (175, 176, 382388), bipolar disorder (389, 390), ASD (391), attention deficit-hyperactivity disorder (392, 393), Tourette syndrome (100, 303, 394), Huntington’s disease (351, 352), depression (174, 395), frontotemporal dementia (36, 396, 397), personality disorder (398), anorexia nervosa (399), temporal lobe damage (400), caudate lesion (401), brain tumor (402), myotonic dystonia (403), and frontal lobe damage [(168, 404, 405); but see Ref. (406)].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple cognitive deficits in SZs include cognitive processes such as attention, working memory, and executive function are correlated with the dysfunctions of distinct brain regions (6). For example, several previous studies (7, 8) have shown that frontal lobe, temporal lobe, parietal lobe, and hippocampus were the core areas associated with cognitive deficits in SZs. Further functional magnetic resonance imaging (fMRI) study showed a decrease in the volume of the prefrontal cortex of SZs compared with that of healthy controls (HCs) (9).…”
Section: Introductionmentioning
confidence: 94%
“…However, the conceptualization of schizophrenia as a neurodevelopmental disorder ( Murray and Lewis, 1987 ) has raised the possibility that ToM impairments may start early on in the developmental pathway, during childhood and adolescence. In fact, an earlier onset of schizophrenia is associated with more pronounced social cognitive deficits in adults ( Linke et al, 2015 ); and impaired ToM performance in adolescents with early-onset-schizophrenia has been described in IQ-matched samples ( Li et al, 2017 ; Tin et al, 2018 ). We recently examined ToM using the "Reading-the-Mind-in-the-Eyes" test, and documented poorer performance in adolescent patients two years after psychosis onset compared to healthy peers ( Ilzarbe et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%